Avaliação histológica e funcional da ampliação vesical com "scaffold" biológico e sintético com e sem semeadura de células tronco mesenquimais derivadas de tecido adiposo. Estudo experimental em coelhos. - Franca, Wagner Aparecido [UNIFESP] (2019)
Objective: Evaluate the histological and functional parameters of bladder enlargement in rabbits with the use of extracellular matrix scaffold and synthetic polyglycolic acid (PGA) scaffold, with and without fat-derived stem cell seeding. Methods: Experimental study which presents 5 groups of nine rabbits: control, extracellular matrix scaffold bladder enlargement with fat-derived stem cell seeding, extracellular matrix scaffold bladder enlargement without stem cell seeding, scaffold bladder enlargement with polyglycolic acid and stem cell seeding and finally group of scaffold bladder enlargement of polyglycolic acid without stem cell seeding. Bladder function was evaluated by analysis of maximal cystometric capacity and bladder capacity in detrusor pressure of 40 cmH20, by urodynamic study and histology, both on the fourth, eighth and twelfth week. Histological analysis was performed with hematoxylin and eosin (H&E) staining to verify the inflammatory reaction (rejection) with the counting of polymorphonuclear cells, lymphocytes, macrophages and foreign body giant cell. Masson's trichrome staining was used to verify the formation of fibrosis through the collagen area. The stem cell used was derived from fat collected from the inguinal region of the rabbit and grown in culture medium. Results: Significant changes in the eighth and twelfth week, (p = 0.032) and (p = 0.033), respectively, in polymorphonuclear cells, foreign body giant cells, macrophages and lymphocytes did not show a rejection-like inflammatory reaction that can occur in clinical transplantation, although they are increased. Collagen analysis showed no statistical difference in the studied groups, the fibrosis areas were equal to the control group. In the functional analysis of variance of pre-cystoplasty and post-cystoplasty bladder compliance, between groups, there were significant increases in the scaffold and PGA groups both seeded with mesenchymal stem cell, demonstrating that the technique allows the improvement of bladder capacity in detrusor pressure of 40 cmH20 (p = 0.049 and p = 0.013, respectively). Cystometric capacity showed no significant increase but showed a tendency to increase in the PGA group seeded with stem cell. Conclusions: Bladder enlargement techniques with implantation of extracellular matrix and PGA scaffolds, seeded or not seeded with fat-derived mesenchymal stem cell, did not generate a deleterious inflammatory reaction, called rejection, and increased bladder capacity in detrusor pressure 40 cmH20. The use of stem cells decreases inflammatory reaction in the enlarged bladder with scaffolds.